Changes in Expression and Cellular Localization of Rat Skeletal Muscle ClC-1 Chloride Channel in Relation to Age, Myofiber Phenotype and PKC Modulation - Conte, Elena; Fonzino, Adriano; Cibelli, Antonio; De Benedictis, Vito; Imbrici, Paola; Nicchia, Grazia Paola; Pierno, Sabata; Camerino, Giulia Maria (Frontiers in Pharmacology, 2020)
The ClC-1 chloride channel 1 is important for muscle function as it stabilizes resting membrane potential and helps to repolarize the membrane after action potentials. We investigated the contribution of ClC-1 to adaptation of skeletal muscles to needs induced by the different stages of life. We analyzed the ClC-1 gene and protein expression as well as mRNA levels of protein kinase C (PKC) alpha and theta involved in ClC-1 modulation, in soleus (SOL) and extensor digitorum longus (EDL) muscles of rats in all stage of life. The cellular localization of ClC-1 in relation to age was also investigated. Our data show that during muscle development ClC-1 expression differs according to phenotype. In fast-twitch EDL muscles ClC-1 expression increased 10-fold starting at 7 days up to 8 months of life. Conversely, in slow-twitch SOL muscles ClC-1 expression remained constant until 33 days of life and subsequently increased fivefold to reach the adult value. Aging induced a downregulation of gene and protein ClC-1 expression in both muscle types analyzed. The mRNA of PKC-theta revealed the same trend as ClC-1 except in old age, whereas the mRNA of PKC-alpha increased only after 2 months of age. Also, we found that the ClC-1 is localized in both membrane and cytoplasm, in fibers of 12-day-old rats, becoming perfectly localized on the membrane in 2-month-old rats. This study could represent a point of comparison helpful for the identification of accurate pharmacological strategies for all the pathological situations in which ClC-1 protein is altered.